The Teologi dan Pedagogik dalam Praktik Pengembangan Kurikulum Gereja: Integrasi Teologi dan Pedagogi dalam Praktik Pengembangan Kurikulum Gereja - Analaura, kristi; Tumpal Sirait, Nehemia; Horo, Korlina (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This research is motivated by an in-depth exploration of the integration of theology and pedagogy in the practice of church curriculum development. Theology and pedagogy are expected to have synergy in realizing optimal curriculum development. The purpose of this study is to review and examine the extent of integration between theology and pedagogy in the practice of church curriculum development. The method used in this research is qualitative with a literature study approach in which the researcher collected primary data from trusted and reputable library sources, as well as secondary data to support the objectivity of this research. The results of this study indicate that the integration of theology and pedagogy in the practice of church curriculum development still appears to be gaps and has not been optimally reflected in the current curriculum development. From this research, it is hoped that each church can understand itself as a central role in implementing and developing the curriculum through the integration of theology and pedagogy so that education and life are realized based on contextual Christian values.